Application of GIS, GPS and Remote Sensing Technologies in forest Management: a Case Study of Chhattisgarh - Bebarta, Kailash Chandra (Indian Forester, 2008)
Developing an information base is a sine-qua-non for scientific management of forests. It requires building a comprehensive geo-database of forest resources and it critical analysis on a continuous basis. This is possible if modern technologies such as computing, geographical information system, geographical positioning system, remote sensing and internet are applied in forest management practices. Towards this, Forest Department of Chhattisgarh has launched an initiative to develop multiplayered geodatabase primarily focused on forest management. It has also prepared an application software known as Working Plan Decision Support System (WP DSS) fully adapted to processes and procedures provided in the new working plan code issued by Govt. of India. GIS and Remote Sensing technologies are fully applied not only to revise forest working plans in the state but also to carry out other management tasks.